The capacity of neurological pupil index to predict absence of somatosensory evoked potentials after cardiac arrest—A study protocol. Issue 6 (29th March 2021) - Lilja, Linus; Thuccani, Meena; Joelsson, Sara; Nilsson, Josefin; Redfors, Petra; Lundgren, Peter; Rylander, Christian
Abstract: Background: Anoxic‐ischemic brain injury is the most common cause of death after cardiac arrest (CA). Robust methods to detect severe injury with a low false positive rate (FPR) for poor neurological outcome include the pupillary light reflex (PLR) and somatosensory evoked potentials (SSEP). The PLR can be assessed manually or with automated pupillometry which provides the neurological pupil index (NPi). We aim to describe the interrelation between NPi values and the absence of SSEP cortical response and to evaluate the capacity of NPi to predict the absence of cortical SSEP response in comatose patients after CA. Methods: A total of 50 patients will be included in an explorative, prospective, observational study of adult (>18 years) comatose survivors of CA admitted to intensive care in a university hospital. NPi assessed with a hand‐held pupillometer will be compared to SSEP signals recorded >48 hours after CA. Primary outcomes are sensitivity, specificity, and odds ratio for NPi to predict bilateral absence of the SSEP N20 signal, with NPi values corresponding to <5% FPRs of SSEP absence. Secondary outcomes are the PLR and SSEP sensitivity, specificity, and odds ratio for poor neurological outcome at hospital discharge and death at 30 days. Discussion: The PLR and SSEP may have a systematic interrelation, and a certain NPi threshold could potentially predict the absence of cortical SSEP response. If this can be concluded from the present study, SSEP testing could be excluded in certain patients to save resources in the multimodal prognostication after CA. Editorial comment The interrelation between loss of the pupillary light reflex (PLR) and the loss of cortical response to a somatosensory evoked potential (SSEP) in comatose cardiac arrest patients is not known. This exploratory prospective study is designed to evaluate whether a specific degree of attenuated PLR, as measured by semiautomated pupillometry, can predict the bilateral loss of cortical SSEP response in severe anoxic/ischemic brain injury. Such an interrelation between the two methods would enable the use of pupillometry rather than the more resource demanding SSEP for neurologic prognostication in post cardiac arrest patients. Trial registration: ClinicalTrials.gov, NCT04720482, Registered 21 January 2021, retrospectively registered.